Secondhand Smoke Exposure and Inflammatory Markers in Nonsmokers in the Trucking Industry - Chiu, Yueh-Hsiu Mathilda (National Institute of Environmental Health Sciences, 2011)
Background: Few studies have directly assessed the association of secondhand smoke (SHS) with cardiovascular disease–related inflammatory markers, and the findings are inconsistent. Objectives: We assessed the association between SHS exposure and the inflammatory markers high-sensitivity C-reactive protein (hs-CRP), interleukin-6 (IL-6), and soluble intercellular adhesion molecule-1 (sICAM-1) in 199 nonsmoking U.S. trucking industry workers. Methods: Participants provided blood samples either by mail (blood drawn at local health care provider near home) or at the work site (blood drawn by research staff on-site) and completed a health and work history questionnaire at the time of blood draw. Exposure to SHS was measured by plasma cotinine concentrations. We used multivariate regression analyses to assess the associations between levels of cotinine and inflammatory markers. Results: The median cotinine level was 0.10 ng/mL (interquartile range, 0.04–0.23 ng/mL). The odds ratios of elevated hs-CRP (above highest CRP tertile, 1.5 mg/L) were 2.85 [95% confidence interval (CI), 1.03–7.89] for the high-cotinine group (> 0.215 ng/mL) and 2.80 (95% CI, 1.11–7.10) for the moderate-cotinine group (0.05–0.215 ng/mL), compared with the low-cotinine group (< 0.05 ng/mL), adjusting for age, sex, race, educational level, obesity, previous smoking history, job title, and medical history. Plasma cotinine levels were not associated with IL-6 or sICAM-1. Conclusions: SHS exposure, as assessed by plasma cotinine, was positively associated with hs-CRP in this group of blue-collar workers. The strength of the association with hs-CRP depended on the cut points selected for analysis.